Alterations in the neuroendocrinological stress response to acute psychosocial stress in adolescents engaging in nonsuicidal self-injury - Kaess, Michael; Hille, Markus; Parzer, Peter; Maser-Gluth, Christiane; Resch, Franz; Brunner, Romuald (Psychoneuroendocrinology, 2012)
Summary: Objective:To investigate the neuroendocrinological stress response to acute psychosocial stress in a clinical sample of female adolescents engaging in nonsuicidal self-injury (NSSI). Methods: The Trier Social Stress Test (TSST), a standardized psychosocial stress protocol, was performed in 14 female patients who engaged in NSSI and 14 healthy control subjects. NSSI was assessed by the Functional Assessment of Self-Mutilation (FASM). Salivary cortisol, heart rate, and affective states, assessed by the Positive and Negative Affect Schedule (PANAS), were measured during the TSST. Results: We found an attenuated cortisol response to acute psychosocial stress in female adolescents with NSSI, whereas no group differences were observed in heart rate and emotional response to the TSST. Conclusions: These findings indicate that the HPA axis is hyporesponsive in adolescents with NSSI. Therefore, reduced secretion of cortisol could play a role in promoting vulnerability of these individuals to acute stress and maladaptive stress responses.